Self‐Healing, Robust, and Stretchable Electrode by Direct Printing on Dynamic Polyurea Surface at Slightly Elevated Temperature. (20th April 2021) - Liu, Shuqi; Chen, Song; Shi, Wei; Peng, Zefei; Luo, Kaiying; Xing, Shuting; Li, Jiatian; Liu, Zunfeng; Liu, Lan
Abstract: Printed electronics on elastomer substrates have found wide applications in wearable devices and soft robotics. For everyday usage, additional requirements exist for the robustness of the printed flexible electrodes, such as the ability to resist scratching and damage. Therefore, highly robust electrodes with self‐healing, and good mechanical strength and stretchability are highly required and challenging. In this paper, a cross‐linking polyurea using polydimethylsiloxane as the soft segment and dynamic urea bonds is prepared and serves as a self‐healing elastomer substrate for coating and printing of silver nanowires (AgNWs). Due to the dynamic exchangeable urea bond at 60 °C, the elastomer exhibits dynamic exchange of the cross‐linking network while retaining the macroscopic shape. As a result, the AgNWs are partially embedded in the surface of the elastomer substrate when coated or printed at 60 °C, forming strong interfacial adhesion. As a result, the obtained stretchable electrode exhibits high mechanical strength and stretchability, the ability to resist scratching and sonication, and self‐healing. This strategy can be applied to a variety of different conducting electrode materials including AgNWs, silver particles, and liquid metal, which provides a new way to prepare robust and self‐healing printed electronics. Abstract : A concept involving preparing stretchable, robust, and self‐healing electrodes via a direct surface printing on a polyurea elastomer is developed in this work. Taking advantage of the dynamic polyurea's kinetic chain movement at an elevated temperature, variable conductive nano‐fillers can be self‐embedded into the elastomer's surface without shape changing, exhibiting high significance in designing both robust and self‐healing electrodes.